2021
DOI: 10.1111/aos.14760
|View full text |Cite
|
Sign up to set email alerts
|

Role of somatic mutations and chromosomal aberrations in the prognosis of uveal melanoma in a Spanish patient cohort

Abstract: Background Uveal melanoma (UM) has a high tendency to cause liver metastases. Metastatic disease is fatal, with a low survival rate. There are two large groups of UMs that, according to their risk of metastatic disease, can be divided into risk subgroups based on histopathological, cytogenetic and molecular characteristics. The presence of somatic mutations in certain genes may explain the origin and prognosis of these tumours. Methods Forty‐six UM samples previously classified as high or low metastatic risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
6
2
Order By: Relevance
“…In our study, we found a statistically significant association between the presence of GNA11 mutation and longer PFS (P = 0.0317); however, our sample size is small. [4,24,25,28,32,33,40]. In our study group, we did not detect an association between GNAQ mutations and survival.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In our study, we found a statistically significant association between the presence of GNA11 mutation and longer PFS (P = 0.0317); however, our sample size is small. [4,24,25,28,32,33,40]. In our study group, we did not detect an association between GNAQ mutations and survival.…”
Section: Discussioncontrasting
confidence: 72%
“…UM often harbor mutations affecting GNAQ (34-58%), GNA11 (21-59%), PLCB4 (0-3%), or CYSLTR2 (0-6%), initiating mutations that are members of the G-protein alpha q signaling cascade; and BAP1 (35-91%), SF3B1 (16-37%), and EIF1AX (0-13%), progression mutations (Table 3) [3,4,8,[14][15][16][17][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In our cohort, the frequency of GNAQ, GNA11, PLCB4, carcinogenesis initiating genes, was similar to those of published literature (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of GNAQ/GNA11 mutations is approximately 80-90% of the UM cases [18,20,21]. In the scientific literature, the frequencies of GNAQ mutations have been reported to range from 24.2 to 53.3% and those of GNA11 mutations from 24.2 to 60% [20,[28][29][30][31]. In previous studies, non-Caucasian populations have shown reduced mutation frequencies in these two genes, but more recent studies have shown that mutations in this population may be closer to the frequencies previously mentioned [32,33].…”
Section: Gna11 Genesmentioning
confidence: 99%
“…Contrastingly, in the GNAQ gene, a one-base change at codon 209 (CAA) can predict the substitution of glutamine by leucine (A > T, p.Q209L) and proline (A > C, p.Q209P), in most cases [17,28]. In exon 5, other mutations, including p.Q209M, p.Q209H, p.Q209I, p.F228L, and p.M203V in GNAQ and p.Q209Y, p.E234K, p.E221D in GNA11, have also been described [28,30] (Table 1). Overall, the frequency of mutations in the exon 4 of GNAQ and GNA11 genes is lower.…”
Section: Gna11 Genesmentioning
confidence: 99%
“…For UM however, this is less evident. Recurrent mutations in BAP1, SF3B1 and EIF1AX, have been found in UM but none are as common as the presence of GNAQ/11 [35][36][37][38][39][40][41][42][43][44]. This shows that there are multiple second hits possible, allowing the tumour to divert into different directions and become (intertumorally) heterogeneous with distinct clinical and pathological behaviour.…”
Section: The Development Of Uveal Melanoma Secondary Mutations In Uveal Melanoma Developmentmentioning
confidence: 99%